Halotolerant/alkalophilic bacteria associated with the cyanobacterium arthrospira platensis (nordstedt) gomont that promote early growth in sorghum bicolor (l.) moench (2012)
Arthrospira platensis associated bacteria (APAB) identified through molecuar biology like Bacillus okhensis, Indibacter alkaliphilus and Halomonas sp., are also producing 3-indol acetic acid (IAA), these bacteria was used in early plant growth promotion tests over Sorghum bicolor, these bioassay was considered indirect evidence to suggest that APAB also may have stimulatory effects over A. platensis growth naturally. I. alkaliphilus and B. okhensis enhanced early germination of S. bicolor seads, with better results than that achieved by Azospirillum brasilense, bacterium used like reference as a common plant growth promoting rizobacteria. The three APAB enhanced significative differences (P≤0.05) over morphoagronomic parameters, I. alkaliphilus and B. okhensis exhibit better resoults in elongation stimulation and root and foliage dry weight. Above evidence suggest this bacteria like plant growth promoting and it recomended testing with A. platensis axenic cultures and its associated bactteri for understanding true interaction between them.